Human-technology relations in an age of surveillance capitalism: Towards an anthropological theory of the dialectic between analogue and digital humanity - Vito Laterza (EtnoAntropologia, 2022)
What can anthropology contribute to the current debates about the negative effects of social media on people? Starting from a critique of anthropological work that sees human subjectivity and culture as ontologically unaffected by social media use, I propose that human engagement with these digital technologies produces significant ontological transformations that deserve more attention. I develop my analysis in dialogue with Boellstorff’s ontology of the digital, Nardi’s theorisation of virtuality and affordances, and Zuboff’s formulation of surveillance capitalism, and I use empirical illustrations from the Cambridge Analytica data scandal to highlight key theoretical junctures. My main contribution is an outline of an anthropological theory of the dialectic between what I call analogue humanity and digital humanity. The two are mutually constituted but ontologically distinct. In the current political economy of digitalisation, tech companies are driving a process of increasing substitution of analogue humanity and forms of life with digital ones, as part of their quest for accurate prediction and social engineering of all aspects of human behaviour. While an anti-technology stance is neither practicable nor desirable, anthropologists need to think about how analogue humanity can be preserved and nurtured so that it can avoid ontological extinction.